RETHINKING THE BOOK OF TAHAFUT AL-FALASIFAH: Examining Al-Ghazali’s Argumentative Criticism Against the Thinking of Philosophers - Lubis, Ali Akhbar Abaib Mas Rabbani; Rozi, Fathur (Universitas Islam Indonesia, 2020)
This study explains al-Ghazali’s argumentative criticism in Tahafut al-Falasifah. It aims to analyze the intentions of al-Ghazali’s argumentative refutation of other alleged rational thinkers considered by irfani epistemology as the cause of decline of Islam and to observe the method used by al-Ghazali in his argument. This study is a library research which is included in the qualitative research cluster. The result of study is that the intentions of al-Ghazali’s argumentative criticism are to discuss the twenty errors of Muslim philosophers, namely al-Farabi and Ibn Sina in matters of metaphysical philosophy. The method used by al-Ghazali is also the same as Aristotle’s criticism of Eudoxus, that is attacking Muslim philosophers in terms of the arguments they built, even labelling them as heretics and infidels/apostates. This method is known as argumentum ad hominem because it attacks Muslim philosophers when it comes to argumentation. It is built on the dialectical method of speech or in other terms known as jawab wa su’al which always recalls an imaginary trial.